Integration of positive environmental factors and differentiation of parental figures in social exposome research - Lavín, Valeria; Torrecilla, Pilar; Kwapil, Thomas R.; Barrantes-Vidal, Neus (Frontiers in Psychology, 2025)
BackgroundEarly adversity is well established as a risk factor for poor mental health, but the potential protective role of positive experiences has been scarcely examined. The exposome paradigm provides a comprehensive framework to model the full spectrum of early environmental experiences, capturing both general and specific dimensions of these experiences. This study aimed to (i) develop an Early Social Exposome score integrating positive and negative experiences, and (ii) explore its associations with positive and negative outcomes.MethodsEarly environmental experiences, psychopathology, positive outcomes, and functioning were assessed for 1,181 non-clinical young adults. Iterative exploratory factor analyses were conducted to optimize the modeling of environmental variables. A final Bifactor Confirmatory Factor Analysis was applied to obtain factor scores.ResultsA general score and four specific factors emerged: Positive Experiences, Paternal Adversity, Maternal Adversity, and Role Reversal. The general Early Exposome was associated with higher psychopathology and lower positive mental health and functioning, whereas Positive Experiences showed the opposite pattern. Maternal Adversity was associated with psychopathology, whereas Paternal Adversity, mirroring epidemiological findings, showed a modest relationship with poorer functioning.ConclusionFindings highlight the importance of assessing and integrating positive experiences in exposome research when modeling the early social environment. Its inclusion allowed to capture the significant protective role of positive peer experiences, which probably partially accounts for the heterogeneity of outcomes related to adversity exposures. Additionally, the figure or source of childhood experiences emerged as a relevant factor that should be contemplated in future research along with the nature of experiences.